Tribal Knowledge: Business Wisdom Brewed from the Grounds of Starbucks Corporate Culture - John Moore (USA Kaplan Publishing, 2006)
Without question, Starbucks Coffee is one of the greatest business success stories of the past decade. Since going public in 1992, it has grown yearly revenues to more than $6.5 billion, achieved a stock price increase of more than 6,500%, and opened over 11,000 locations worldwide. But for a company that has accomplished so much, outsiders really know very little about the Starbucks secrets to success. That's because much of the company's sage advice and weathered truisms exist solely in the hearts and minds of longtime Starbucks employees. This so-called "tribal knowledge" includes pithy quotes uttered by Starbucks executives, mantras used by Starbucks project groups, learnings from failed pilot programs, and "ah-ha" moments from successful projects. It's company stories passed down from one generation of employees to the next. It's intense. It's poignant. It's thought provoking. It's actionable. It's a language of Starbucks "tribal knowledge" that has never been written - only spoken - and only within the Starbucks tribe. Until now. In "Tribal Knowledge: Business Wisdom Brewed from the Grounds of Starbucks Corporate Culture," ""longtime Starbucks marketer John Moore shares untold, behind-the-scenes stories of the processes, the programs, and the products that have made Starbucks a remarkable business success, including: - Why Starbucks was purpose driven to make a difference in the world. - How Starbucks goes beyond simply having a mission statement to living its mission statement. - How the Starbucks principled, innovative, and cause-related approach to marketing built an endearing and enduring brand. - Why efforts to extend the Starbucks brand into lifestyle offerings such as a literary magazine and full-service restaurants failed. - How the Starbucks approach to employee career growth has created a passionate workforce. - How to apply the Starbucks "tribal knowledge" to your business, entrepreneurial venture, or project group. "Tribal Knowledge" gives you unprecedented access to the many business lessons that helped Starbucks find prosperity by selling a commodity - all from a marketer who lived inside the Starbucks tribe.
Keywords: Business; Nonfiction; Management; Leadership; Organizational effectiveness; Coffee industry; Marketing; HRM: Contemporary Issues (HRM2074-N )